The effects of eye masks and earplugs on sleep quality, anxiety, fear, and vital signs in patients in an intensive care unit: A randomised controlled study - Turan, Gulcan Bahcecioglu; Gurcan, Fatma; Ozer, Zulfunaz (Wiley, 2024)
In intensive care units, environmental factors like loud noises and bright lights can cause fear, anxiety, changes in vital signs, and sleep disturbances. The aim of this study was to find out how using earplugs and eye masks during the night affected sleep quality, anxiety, fear, and vital signs of patients in an intensive care unit. A total of 70 patients, 35 in the intervention and 35 in the control group, were included in this randomised controlled study. While the patients in the intervention group were provided with earplugs and eye masks for 3 nights in addition to their routine care, only routine care was given to the patients in the control group. The 'Introductory Information Form', 'Visual Analogue Scale-Fear (VAS-F)', 'Visual Analogue Scale-Anxiety (VAS-A)', 'Vital Signs Monitoring Form', and 'Richards-Campbell Sleep Questionnaire' were used for data collection. It was found that the mean scores of VAS-F, VAS-A, heart rate, diastolic and systolic blood pressure of the intervention group decreased significantly after the intervention, while their sleep quality increased significantly. In this study, it was found that using earplugs and eye masks for patients in an intensive care unit during the night was effective in improving patients' sleep quality and reducing fear, anxiety, and problems in vital signs.
Keywords: anxiety; earplug; eye mask; fear; intensive care; sleep quality; vital signs